Real-time data retrieval technique for virtual GIS - Zamri, Muhamad Najib (Penerbit UTM, 2007)
Virtual GIS has been employed as a component in many systems in majority of recent applications. It includes urban planning, virtual tourism, environmental simulation systems, evaluation of vegetation, soil, waterway, or road patterns, disaster prevention, military training, education and many other tasks. There are more than 800 commercial terrain visualization software have been developed by various vendors that involved in GIS field. The usage of 3D spatial data is obviously more effective than conventional 2D databases. It is due to the unique and capabilities of 3D GIS in capable to offer a higher degree of freedom for interactive navigation and increase the level of visual realism of virtual scene. The users are able to move forward and backward, orient and flythrough smoothly around the created world which is identical to the real world. The user friendly interface is important to facilitate the ease of use for professional group such as architects, urban planners and so on to explore the created software and to make sure the accuracy of their developed system is maintained.